Bearing capacity of batter piles embedded in sandy soil. Issue 5 (19th October 2016) - Al-Neami, Mohammed A.; Rahil, Falah H.; Al-Bayati, Khaldoon S.
Abstract : This paper introduces an attempt to examine the effect of batter angle of a single pile model on its ultimate vertical load capacity. A 32-steel solid pile models are used in this research. Three lengths of piles are selected (300, 400, and 500 mm) for embedment ratios (depth to width, L/D ) = 15, 20 and 25, respectively. Batter pile is embedded in three different relative densities of sand (loose, medium and dense sand bed). The constant rate penetration test (CRPT) method was selected using a manufactured driving hammer to install the pile models in a steel box with dimensions 1000, 750 and 700 mm. The vertical load is conducted monotonically by a special hydraulic apparatus. The results indicate there is an optimum batter angle 20° that gave a higher load capacity. Pile load capacity is highly affected by relative density and less affected by L/D ratio.